Influence of psychological factors on product development : lessons from aerospace and other industries - Kamata, Eginaldo Shizuo (Space technology library, 2002)
"This book is primarily intended for engineering and quality professionals who want to know the limitations of current methods used in product development, to examine the so-called soft factors by means of grounded studies of their effect on R & D performance, not only to acknowledge the influence of soft factors but to actively consider their potential to improve the work environment." "Academic researchers of the topic will also find many references and material for advanced courses on project and quality management." "In addition to numerous cases from the aerospace industry, its general solution concepts are generalizable to other industries in which the high degree of product complexity necessitates effective interaction among different disciplines." "The historical evaluation is neither intended for introductory purposes nor to propose a return to the past, but as a survey of the relevant factors to be applied in present and future projects."--Jacket.